INFORMATION ON THE EDUCATION SYSTEM OF FOREIGN COUNTRIES - A. A. Jalilov (Modern American Journals, 2025)
The education system in Japan The formation of Japanese education began in 1867-1868. Japan set itself two tasks: the first - enrichment, the second - the introduction of Western technology into Japanese production, and in order to achieve this, it was stated that, first of all, the education system needed to be radically changed. In 1872, the "Law on Education" was adopted. In this, Japanese education was harmonized with Western education. In 1908, primary education in Japan was made compulsory for 6 years. In 1893, the first vocational college appeared. The Constitution adopted in 1946 defined the rights and duties of citizens in the field of education. It stipulated that all children should receive free general education.